Empirical study on the relationships of internet banking quality, customer value, and customer satisfaction - Umbas Krisnato (Expert journal of marketing, 2017)
The purpose of this conducted study was to test the direct and indirect effects of internet banking quality and customer value to customer satisfaction. This study uses descriptive analysis and multiple regression analysis to examine these relationships. The study is based on a survey conducted with respondents who use internet banking in their day-to-day activities, and all questionnaire items are deemed valid and reliable. For data analysis, the descriptive analysis for the indicators, dimensions, and variables proved to be in a good category. Research findings and implications of the regression analysis show that internet banking quality and customer value had a greater direct impact on customer satisfaction, rather the partial relationships of these variables to satisfaction. In the partial relationships, customer value has a higher influence on customer satisfaction, than internet banking quality. As a research recommendation, banks should provide a more humanistic internet banking service for better consumer satisfaction. A major research limitation of the study is that it does not measure service quality of internet banking, and only focuses on customers of internet banking use of one single bank. The originality of this research relies on the insights of internet banking quality leading to customer satisfaction and increasing the value of a bank to its main target markets.
2758454-9; 2344-6773; Expert journal of marketing; 778946770